(untitled) (Environment & Health, 2022)
Objective: We compared the antimicrobial efficacy of different types of UV radiators. Materials and methods: In the work, we used the ultraviolet radiators of various types and manufacturers recommended for disinfection of air and surfaces of the premises. The effectiveness of surface disinfection from the test microorganisms Staphylococcus aureus and Pseudomonas aeruginosa was established by the Regulations “Methods for testing disinfectants to assess their safety and effectiveness". We determined a total number of aerobic microorganisms and molds according to the State Pharmacopoeia of Ukraine 2.0, p. 2.6.12. Results: The efficacy of the use of ultraviolet radiation for disinfection of the surfaces with the most resistant representatives of gram-negative and gram-positive microorganisms using a portable "Individual ultraviolet irradiator ALED UVC-1W" for 1 min. was established. The disinfection effect was 4.02 lg for S. aureus and 4.08 lg for P. aeruginosa. The effective action of the bactericidal ultraviolet radiation with the use of open-type radiators (with louvers) "UV-BLAZE" was demonstrated. A decrease of the total number of microorganisms, including molds in the air, by a factor of 36 (room № 1) and 136 (room № 2) was noted. Disinfection of the surfaces in the premises for the similar indicators was 98.6% and 99.5%, respectively. A decrease in the level of microbiological air pollution in the premises, when using LED radiation with the open-type ALED T5NXXX UVC-5W-01 luminaires for a long period of time (8 hours), was noted. The disinfection efficacy was 77% for bacteria and 83.3% for fungi.